2017
DOI: 10.21276/apalm.1516
|View full text |Cite
|
Sign up to set email alerts
|

Histopathological and Histomorphometric analysis of Pancreas and liver of diabetic rats treated with MucunaPruriens seed extract.

Abstract: Background: Medicinal plants play a major role in controlling diabetes by producing microstructural changes in liver and pancreas. Quantification of islets and hepatocytes by using histomorphometric tools are effective in evaluating the antidiabetic action of drugs. Aims and Objectives:To assess the anti diabetic properties of alcoholic extracts of Mucuna Pruriens seeds (200 mg/kg b.w) by means of histological and histomorphometric analysis of pancreas and liver .Methods: Seventy two neonatal wistar rats were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 12 publications
2
3
0
1
Order By: Relevance
“…The typical sign of Non-Alcoholic Fatty Liver Disease (NAFLD) is vacuolations and inflammations 19 , which was obvious in the current study. Kidneys showed structural changes in the PCT and the Glomerulus with mononuclear infiltrations.…”
Section: Group I Group Ii Fig 1: Hande Stained Sections Of Kidneys Group I Normal Control Group Ii Fructose Group G-glomerulus (Yellow) Psupporting
confidence: 50%
“…The typical sign of Non-Alcoholic Fatty Liver Disease (NAFLD) is vacuolations and inflammations 19 , which was obvious in the current study. Kidneys showed structural changes in the PCT and the Glomerulus with mononuclear infiltrations.…”
Section: Group I Group Ii Fig 1: Hande Stained Sections Of Kidneys Group I Normal Control Group Ii Fructose Group G-glomerulus (Yellow) Psupporting
confidence: 50%
“…The number of healthy and necrotic hepatocytes were determined by direct counting method at 40X magnification using the ocular grid. The total number of healthy and necrotic hepatocytes was expressed as N/1000 μm 2 of the hepatic parenchyma (Rajesh et al, 2017).…”
Section: Histomorphometric Analysismentioning
confidence: 99%
“…Tannins are important phytochemical compound that possess antioxidant properties [19]. Flavonoids possess membrane stabilizing properties and inhibit lipid peroxidation in liver, brain, pancreas etc [20]. Phenols have antioxidant properties which carry out their protective activity on cells either by checking the free radical generation or by scavenging the free radicals [21].…”
Section: In Vitro Dpph Antioxidant Assaymentioning
confidence: 99%
“…Phenols have antioxidant properties which carry out their protective activity on cells either by checking the free radical generation or by scavenging the free radicals [21]. Various studies have reported the antioxidant and anti-inflammatory potentials of saponins [22,23]. Bioactive components like alkaloids and phytosterols are also considered effective in conditions like stress and depression [24].…”
Section: In Vitro Dpph Antioxidant Assaymentioning
confidence: 99%